ANALISIS KIMIA DAN FISIK MIE BASAH DARI TEPUNG MOCAF (MODIFIED CASSAVA FLOUR) DENGAN PENAMBAHAN TEPUNG TAPIOKA DAN EKSTRAK DAUN KELOR (Moringa oleifera) - Rahmawati, Fernanda Indi; asmoro, novian wely; Tari, Agustina Intan Niken (Fakultas Teknologi Pangan dan Agroindustri, Universitas Mataram, 2023)
MOCAF is flour from cassava which is processed using the principle of modifying cassava cells by fermentation using Lactic Acid Bacteria (LAB). Mocaf flour can be used as an ingredient for wet noodles because it has the same swelling power as wheat flour but has a texture that is difficult to shape because it does not contain gluten. To overcome this, it needs to be formulated with tapioca flour to bind the dough and Moringa leaf extract as a natural coloring. This study used RAL 1 factor, namely the formulation using mocaf flour, tapioca flour, and Moringa leaf extract (F1=95%:5%, F2=85%:15%, F3=75%:25%, F4=65%:35 %, F5=55%:45%) for the Moringa leaf formulation of 20 ml from 100g of flour. The data obtained was analyzed statistically by One Way Anova followed by a significant difference test with Duncan with a significance level of 5%. Observation parameters include water content, ash content, elasticity, cooking time, rehydration power, and cooking loss. The formulation using mocaf flour, tapioca flour, and Moringa leaf extract did not have a significant effect on the water content and ash content of the wet noodles. The water content of wet noodles ranges from 37.53% to 38.34%. The ash content of wet noodles ranges from 1.53% to 2.07%. The formulation using mocaf flour, tapioca flour and Moringa leaf extract has a significant effect on elasticity, cooking time and rehydration capacity but has no significant effect on cooking loss.